Gender stereotyping in church and community : a Nigerian feminine perspective - Onwunta, Ijeoma Esther (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DTh (Practical Theology and Missiology))--University of Stellenbosch, 2009.